CPOLYMESH: Matlab and Python codes for complex polynomial approximation by Chebyshev admissible meshes - Kenne, Dimitri Jordan; Sommariva, Alvise; Vianello, Marco (Journal of Approximation Software, 2024)
We provide Matlab and Python codes for polynomial approximation on complex compact sets with connected complement, by Chebyshev-like admissible polynomial meshes on boundaries with piecewise (trigonometric) polynomial parametrization. Such meshes have lower cardinality with respect to those previously known. They are used for polynomial least-squares, for the extraction of extremal interpolation sets of Fekete and Leja type, as well as for the computation of the uniform norms (Lebesgue constants) of polynomial projection operators.